LncRNA NEXN-AS1 Serves as a Diagnostic Biomarker for Carotid Artery Stenosis, Forecasting Cerebral Ischemic Events - Weilong Liu MM; Dandan Jia MM; Lijun Yang MM; Zhenzeng Fan MD (Clinical and Applied Thrombosis/Hemostasis, 2025)
Objective Carotid artery stenosis (CAS) is a significant contributor to cerebral ischemic events (CIEs). This study investigated the expression pattern and clinical significance of lncRNA NEXN-AS1 in CAS and CIEs. Methods 132 patients with CAS and 98 controls were enrolled. RT-qPCR was employed to quantify serum levels of NEXN-AS1 and miR-92a-1-5p. The diagnostic utility of NEXN-AS1 for CAS was assessed using ROC curves. Logistic regression pinpointed potential risk factors for severe CAS. Patients were followed for 2 years, and Kaplan-Meier and Cox methods evaluated the prognostic role of NEXN-AS1 and risk factors for CIEs in CAS cases. RIP and DLR assays were conducted to confirm the association between NEXN-AS1 and miR-92a-1-5p. Results Serum NEXN-AS1 was less expressed in CAS patients than in controls, which could effectively distinguish between the two groups with high sensitivity and specificity. CAS patients with severe stenosis had lower serum NEXN-AS1 levels than those with moderate stenosis. Patients with low NEXN-AS1 expression were more prone to developing CIEs compared to those with high expression (log-rank P = .0051). Cox regression analysis identified NEXN-AS1 as an independent risk factor for the development of CIEs. Molecularly, the target of NEXN-AS1 is miR-92a-1-5p. Conclusion Patients with low NEXN-AS1 expression could serve as diagnostic indicators for CAS and may predict the occurrence of CIEs. This study may offer new insights into the management of CAS and CIEs.